Impacts of novel calotropis gigantea seed biodiesel usage as a fuel substitute along with various metal-oxide nanoparticles on the DICI engine characteristics - T. Sathish; Ümit Ağbulut; P. Suresh Kumar; S.D. Uma Mageswari; N. Stalin; R. Pandian; Mohd Ubaidullah; Jayant Giri; Shoyebmohamad F. Shaikh (Case Studies in Thermal Engineering)
Calotropis gigantea, commonly known as Indian milkweed, is a prevalent plant in Asia. It typically thrives in open and unused areas, often considered a weed. This plant produces flowers and fruits consistently throughout the year, exhibiting a continuous flowering and fruiting cycle. This research investigated the viability of Calotropis gigantea seed oil as a potential source intended for biodiesel manufacturing. The oil was obtained from Calotropis gigantea seeds using hexane extraction in the Soxhlet apparatus. The seeds were determined to contain 33.3 wt% of oil content. The process of biodiesel production involved conducting a transesterification reaction. Further, the produced biodiesel was blended with pure diesel and three different nanoparticles, Titanium dioxide (TiO2), Chromium oxide (Cr2O3), and Silicon dioxide (SiO2), to evaluate combustion performance, and emission characteristics of a single-cylinder diesel engine under various load conditions. Incorporating Cr2O3 nanoparticles into the CGSB20 biodiesel blend yielded significant improvements in BTE, coupled with BSFC reduction. Specifically, in the CGSB20 + Cr2O3 fuel mixture, BTE increased notably by 31.2 %, reaching a value of 0.33 g/kWh for BSFC. Similarly, for the CGSB20 + SiO2 and CGSB20 + TiO2 blends, BTE experienced enhancements of 29.2 % and 28.1 %, respectively, while BSFC values were lowered to 0.37 and 0.4 g/kWh. Furthermore, the unchanging dispersal of nanoparticles within the CGSB20 blend exhibited extraordinary cylinder pressure and HRR values, reaching 77 bar and 34.2 J/CA, respectively. The CGSB20+ Cr2O3 blend yielded favorable emissions outcomes. Specifically, CO, NOx, UHC, and smoke emissions were approximately 4.5 g/kWh, 725 ppm, 0.11 g/kWh, and 23.6 %, respectively.